Production and characterization of monoclonal antibodies for the detection of the hepatitis C core antigen - Vidal-Alcántara, Erick Joan; Mas, Vicente; Yélamos, María Belén; Gómez, Julián; Amigot-Sánchez, Rafael; Resino, Salvador; Martinez, Isidoro (Frontiers in Molecular Biosciences, 2023)
Background: Despite highly effective treatments to cure hepatitis C, almost 80% of chronically HCV-infected people are not treated, as they are unaware of their infection. Diagnostic rates and linkage to care must be substantially improved to reverse this situation. The HCV core antigen (HCVcAg) is a highly conserved protein that can be detected in the blood of HCV-infected patients and indicates active infection. Aim: To produce murine monoclonal antibodies against HCVcAg suitable for rapid and inexpensive tests to detect HCV infection. Methods: BALB/c mice were sequentially inoculated with purified recombinant HCVcAg from Gt1a, Gt3a, Gt4a, and Gt1b genotypes. Hybridomas producing the desired monoclonal antibodies were selected, and the reactivity of antibodies against HCVcAg from various genotypes was tested by Western blotting and dot blotting. The binding kinetics of the antibodies to purified HCVcAg was analyzed by surface plasmon resonance (SPR), and their ability to detect HCVcAg was tested by double antibody sandwich ELISA (DAS-ELISA). Results: Four specific monoclonal antibodies (1C, 2C, 4C, and 8C) were obtained. 1C, 2C, and 4C recognized HCVcAg of all genotypes tested (Gt1a, Gt1b, Gt2a, Gt3a, and Gt4a), while 8C did not recognize the Gt2a and Gt3a genotypes. Based on SPR data, the antibody-HCVcAg complexes formed are stable, with 2C having the strongest binding properties. DAS-ELISA with different antibody combinations easily detected HCVcAg in culture supernatants from HCV-infected cells. Conclusion: Specific and cross-reactive anti-HCVcAg monoclonal antibodies with strong binding properties were obtained that may be useful for detecting HCVcAg in HCV-infected samples.